Preamble to the aesthetic qualities of ceramic mural designs in interior design (Journal of the College of Basic Education, 2022)
The ancient civilization of Mesopotamia, through its multiple eras, created for us a lot of design innovations. The art of ceramic murals is one of the oldest evidences of its civilization, as it provided us with messages recorded in calligraphy and color, which revealed to us, with its components, an enlightening diversity. To the extent that these creative designs are characterized by artistic and technical preambles, they came connected with myths and beliefs full of secrets, as they included in their constructive record many One of the intellectual contents and the aesthetic civilization that preoccupied the characteristics of design thought widely, and the sensory effects it contained, and its features emerged through the preambles of the aesthetic characteristics of the designs of the interior spaces, so that it had a clear impact on the recipient.